2008
DOI: 10.1086/529583
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Dust in the Intracluster Medium from Reddening of Background Galaxies

Abstract: We report a search for the presence of dust in the intra-cluster medium based on the study of statistical reddening of background galaxies. Armed with the Red Sequence Cluster survey data, from which we extracted (i) a catalog of 458 clusters with z clust < 0.5 and (ii) a catalog of ∼ 90,000 galaxies with photometric redshift 0.5 < z ph < 0.8 and photometric redshift uncertainty δz ph /(1 + z ph ) < 0.06, we have constructed several samples of galaxies according to their projected distances to the cluster cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 51 publications
16
34
1
Order By: Relevance
“…The comparison with the IR-SFR to X-ray luminosity ratios measured for the two clusters Coma and MS1054-0321 (Bai et al 2007a) confirms that the measured SFR may be insufficient to explain the high IR to X-ray luminosity ratio derived by our stacking analysis. Moreover, our upper limit to the dust in the ICM is of the same order as that measured by Muller et al (2008) from their search for statistical reddening of background galaxies behind a sample of 458 RCD clusters with z < 0.5. Their extinction value converted into an upper limit to the dust mass within the central Mpc is 8 × 10 9 M .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The comparison with the IR-SFR to X-ray luminosity ratios measured for the two clusters Coma and MS1054-0321 (Bai et al 2007a) confirms that the measured SFR may be insufficient to explain the high IR to X-ray luminosity ratio derived by our stacking analysis. Moreover, our upper limit to the dust in the ICM is of the same order as that measured by Muller et al (2008) from their search for statistical reddening of background galaxies behind a sample of 458 RCD clusters with z < 0.5. Their extinction value converted into an upper limit to the dust mass within the central Mpc is 8 × 10 9 M .…”
Section: Discussionsupporting
confidence: 64%
“…A statistical detection of intracluster dust extinction towards SDSS quasars located behind clusters of galaxies was obtained by Chelouche et al (2007). An upper limit was also derived by Muller et al (2008) by studying the statistical reddening of galaxies behind 458 RCS clusters. Finally, Bai et al (2007b) derived upper limits at 24 and 70 μm from observations by the Spitzer telescope of the cluster Abell 2029 (z = 0.08).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we cannot draw any firm conclusion about the origin of the absorption from this analysis. Both the mini-BAL features in the quasar spectrum (see Oguri et al 2008), which assures the presence of outflows in the sightline of this quasar, and the deficiency of dust in the ICM particularly near the center (Chelouche et al 2007;Muller et al 2008;Bovy et al 2008;Kitayama et al 2009) suggest that intrinsic absorption at the quasar redshift is the more likely scenario, although the anomalous flux ratios imply a faint galaxy near image C which might host the dust at the lens redshift. Indeed, a probable galaxy has recently been identified in the vicinity of image C in the HST image (Oguri et al 2012b), which might cause the extra absorption detected in image C. If the former interpretation is correct, the different absorptions between images B and C probe spatial variations of the absorption content, possibly related to the structure of disk wind outflows (Green 2006).…”
Section: Comparison With Optical and Radio Flux Ratiosmentioning
confidence: 95%
“…They found mean E(B À V ) values of a few ; 10 À3 mag for sight lines passing $1 Mpc from the clusters' centers. However, a recent study found no evidence of dust in 0:2 < z < 0:5 clusters from a photometric study of color excesses in several bands and, assuming a Galactic extinction law, derived an average visual extinction of hA V i ¼ 0:004 AE 0:010 mag (Muller et al 2008).…”
Section: Introductionmentioning
confidence: 97%